Color and Fastness Properties of Woven Stretchable Fabrics - Ali Abu Nassif, Najwa (Journal of Research Updates in Polymer Science, 2017)
Stretchable fabrics have gained much interest in the last few years because their higher comforts and aesthetic properties. The main parameters which control the stretchable fabric properties were found to be spandex linear density and draft ratio. In this research paper, the influences of these variables on color properties of stretchable fabrics were investigated. Color properties of the stretchable fabrics were characterized by whiteness index, K/S values, and colorfastness to washing, rubbing and perspiration. The results of this work showed that color properties of the stretchable woven fabrics were affected by independent variables. Generally, impact of spandex draft ratio on color properties was more pronounced than the effects of spandex linear density.